Effective spermatozoa to egg ratio for artificial insemination in Labeo rohita (Ham.) - Jahageerdar, Shrinivas; Krishna, Gopal; Prasad, J K (Indian Journal of Fisheries, 2011)
The present study was carried out to estimate the minimum effective sperm to egg ratio for rohu (Labeo rohita)for artificial insemination using cryopreserved fish semen. The mean body weights of male and female brooders were 1.25 ±0.002 and  1.48 ± 0.002 kg, respectively. The average quantity of milt produced was 2.18 + 0.006 ml. and the sperm concentration was 2.58 ± 0.16 X 1010 ml-1. The mean number of eggs was 1225 ± 45 per ml. The average fertilization rate obtained with the sperm to egg ratio of 6000:1 was 26.07 ± 2.48; the rates were 48.27 ± 2.77 and 46.55 ± 3.32 for the ratio of 12000:1 and 15000:1, respectively,where-as it was 52.09 ± 3.18% with neat milt. It was found that the sperm to egg ratio of 12000:1 provides an optimum fertilization rate.